Assessment of Mandibular Asymmetries in Adults: A Radiographic Study - Ahmad A Abdulmawjood (University of Mosul, College of Dentistry, 2013)
The mandibular asymmetry is important because of its direct effect on facial appearance. Aims: The aim of the present study was to determine the prevalence and severity of mandibular asymmetries between right and left sides. Materials and methods: The sample consisted of 22 males and 23 females having lateral cephalometric and orthopantomographic radiographs. Four linear and two angular measurements were compared between right and left sides of the mandible. These measurements were: ramus height(RH), ramus width(RW), corpus height(CH), corpus length(CL), gonial angle(Go) and condylar angle(Co). Results: The study revealed no significant differences between right and left sides of the mandible, in both gender, regarding the 4 linear measurements. Whereas for the angular measurements there was a significant difference in condylar angle between right and left sides in both male and female groups. Also no significant gender differences were found regarding all measurements except in corpus height. Conclusion: No significant facial asymmetry was found between right and left sides of the mandible for the population being studied in both genders except in condylar angle. In addition it was found out that severe mandibular asymmetry is not so a common occurrence